Performance and reliability of the Lower Quarter Y Balance Test in healthy adolescents from grade 6 to 11 - Schwiertz, G.; Brueckner, D.; Schedler, S.; Kiss, R.; Muehlbauer, T. (Gait and Posture, 2019)
Background: The Lower Quarter Y Balance Test (YBT-LQ) has been widely used in the field to assess dynamic balance performance in various populations. However, no study has demonstrated test-retest reliability of the YBT-LQ in adolescents including several age cohorts, even though reliability is necessary to provide repeatable performance data. Objective: Thus, we examined test-retest reliability of the YBT-LQ in healthy adolescents. Methods: In a school setting, 178 secondary school students (93 female, 85 male) in sixth to eleventh grades (11-19 years) performed the YBT-LQ twice, 7 days apart. Normalized maximal reach distances (% leg length) for all three directions (i.e., anterior, posterolateral, posteromedial) and both legs and the composite score were used as outcome measures. Intraclass correlation coefficient (ICC3,1) and standard error of measurement (SEM) were calculated to assess relative and absolute test-retest reliability, respectively. Practical relevance of the YBT-LQ was determined by calculating the minimal detectable change (MDC95%). Results: Irrespective of grade, test-retest reliability for all distances reached was predominately "excellent" (i.e., ICC3,1 > 0.75) and the rather small SEM values ranged from 1.77 to 5.81%. Depending on grade and reach direction, MDC values of 4.90 to 16.10% represent the minimum amount of change needed to identify clinically relevant effects in repeated measurements of the YBT-LQ performance. Conclusions: The observed values suggest that the YBT-LQ is a reliable test and suitable to detect changes of dynamic balance performance in healthy adolescents from grade six to eleven (i.e., aged 11-19 years).